Study protocol: a mixed methods feasibility study for a loaded self-managed exercise programme for patellofemoral pain - Smith, Benjamin E.; Hendrick, Paul; Bateman, Marcus; Moffatt, Fiona; Rathleff, Michael Skovdal; Selfe, James; Smith, Toby O.; Logan, Pip (Biomed Central, 2017)
Background: Patellofemoral pain (PFP) is one of the most common forms of knee pain in adults under the age of 40, with a prevalence of 23% in the general population. The long-term prognosis is poor, with only one third of people pain-free 1 year after diagnosis. The biomedical model of pain in relation to persistent PFP has recently been called into question. It has been suggested that interventions for chronic musculoskeletal conditions should consider alternative mechanisms of action, beyond muscles and joints. Modern treatment therapies should consider desensitising strategies, with exercises that target movements and activities patients find fearful and painful. High-quality research on exercise prescription in relation to pain mechanisms, not directed at specific tissue pathology, and dose response clearly warrants further investigation. Our primary aim is to establish the feasibility and acceptability of conducting a definitive RCT which will evaluate the clinical and cost-effectiveness of a loaded self-managed exercise programme for people with patellofemoral pain. Method: This is a single-centred, multiphase, sequential, mixed-methods trial that will evaluate the feasibility of running a definitive large-scale randomised controlled trial of a loaded self-managed exercise programme versus usual physiotherapy. Initially, 8–10 participants with a minimum 3-month history of PFP will be recruited from an NHS physiotherapy waiting list and interviewed. Participants will be invited to discuss perceived barriers and facilitators to exercise engagement, and the meaning and impact of PFP. Then, 60 participants will be recruited in the same manner for the main phase of the feasibility trial. A web-based service will randomise patients to a loaded self-managed exercise programme or usual physiotherapy. The loaded self-managed exercise programme is aimed at addressing lower limb knee and hip weakness and is positioned within a framework of reducing fear/avoidance with an emphasis on self-management. Baseline assessment will include demographic data, average pain within the last week (VAS), fear avoidance behaviours, catastrophising, self-efficacy, sport and leisure activity participation, and general quality of life. Follow-up will be 3 and 6 months. The analysis will focus on descriptive statistics and confidence intervals. The qualitative components will follow a thematic analysis approach. Discussion: This study will evaluate the feasibility of running a definitive large-scale trial on patients with patellofemoral pain, within the NHS in the UK. We will identify strengths and weaknesses of the proposed protocol and the utility and characteristics of the outcome measures. The results from this study will inform the design of a multicentre trial.